A Convenient Method for the Preparation of Losartan Active Metabolite (EXP-3174) - PIRALI-HAMEDANI, MORTEZA; ALIABADI, ALIREZA; SHEKARCHI, M.; AMINI, M.; REZA ROUINI, MOHAMMAD; SHAFIEE, ABBAS; FOROUMADI, ALIREZA (Asian Journal of Chemistry, 2010)
Losartan is an angiotensin antagonist with a 5-carboxylate active metabolite (EXP-3174). This active metabolite is the result of the oxidation of 5-hydroxymethyl group to the corresponding 5-carboxyl group in liver. The active metabolite (EXP-3174) is important in pharmacological and biopharmaceutical studies of parent drug. Therefore, a convenient two steps procedure has been developed based on the oxidation of hydroxymethyl group of losartan to aldehyde and subsequent oxidation to carboxylate using different oxidizing reagents. H2O2-KOH reagent was found the most convenient and efficient method.